A UK clinical audit addressing the quality of prescribing of sodium valproate for bipolar disorder in women of childbearing age. Issue 4 (12th April 2018) - Paton, Carol; Cookson, John; Ferrier, I Nicol; Bhatti, Sumera; Fagan, Elizabeth; Barnes, Thomas R E
Abstract : Objectives: To review prescribing practice concerning valproate, an established human teratogen, for the management of bipolar disorder in women of childbearing age. Design: The Prescribing Observatory for Mental Health conducted a baseline clinical audit in the UK, as part of a quality improvement programme. Participants: Six hundred and forty-eight clinical teams from 55 mental health Trusts submitted retrospective treatment data relating to patients with a diagnosis of bipolar disorder. Results: Of the audit sample of 6705 patients, 3854 were 50 years of age or younger. Valproate was prescribed for 24% of women and 43% men in this age group, and the mean dose of valproate was lower in women (1196 mg) than in men (1391 mg). For only half of such women was there documented evidence that information had been provided on the risks for the unborn child and the need for adequate contraception. Valproate was more often used in men to treat mania and aggression, while the most common treatment targets in women were hypomania and relapse prevention. Conclusions: Despite explicit recommendations in national treatment guidelines and published safety alerts and warnings regarding the use of valproate in women of childbearing age, current prescribing of this medication to such women in the context of the treatment of bipolar disorder falls short of best practice, particularly with regard to provision of information regarding the risks associated with exposure to valproate during pregnancy. While women younger than 50 years of age were less likely to be prescribed valproate than men in the same age group, and at a lower dosage, it is unclear to what extent this reflects clinicians' concerns about teratogenicity or is driven by perceptions of the indication for valproate, and the dosage required, for the treatment of different phases of the disorder in men and women.